Introduction à la bioéthique - Parizeau, Marie-Hélène (Assurances, 1984)
We asked Mrs. Marie-Hélène Parizeau to allow us to quote from her introduction to bio-ethics, included in the thesis for a mastership submitted to the University of Montreal. We thought that the subject was of such interest that we would like to make an article from the subject matter of the thesis. Mrs. Parizeau looks at euthanisia, in vitro conception and other subjects which pose serious challenges to our evolving society.